PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS XI MIPA 1 SMA BABUSSALAM PEKANBARU - Angraini, Resi Yuli; Syofni, Syofni; Jalinus, Jalinus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
outcomes of students of class XI MIPA 1 SMA Babussalam Pekanbaru odd semester of the academic year 2017/2018. Form of research conducted is action research (PTK) with 2 cycles. The research subjects consisted of 24 female students and 6 male students with heterogeneous ability. The research data collection instrument is an observation sheet used to obtain teacher and student activity data during the learning process and the mathematics learning result test. The observation sheet was analyzed descriptively narrative, while the test of learning result was analyzed by descriptive statistic. Based on the data analysis of teacher and student activity after applying Discovery Learning, teacher and student activity started to run well and experienced improvement at each meeting. Based on the data analysis of student learning outcomes, there is an increase in student learning outcomes in each cycle. Based on the analysis of KKM achievement, the number of students who reached KKM at UH 1 amounted to 27 people with the percentage of 90% and UH 2 was 28 people with the percentage of 93%. Based on the frequency distribution analysis, an increase in the number of students who scored above the KKM. From this research, it can be concluded that the application of Discovery Learning models, can improve the learning process and also can remind students of mathematics learning result of grade XI Science 1 of Babussalam Senior High School Pekanbaru. Keywords: Mathematics learning outcomes, Discovery Learning models, Classroom Action Research.